2020
DOI: 10.21475/ajcs.20.14.08.p2405
|View full text |Cite
|
Sign up to set email alerts
|

Stress-resilient maize for climate-vulnerable ecologies in the Asian tropics

Abstract: Most parts of the Asian tropics are hotspots of climate change effects and associated weather variabilities. One of the major challenges with climate change is the uncertainty and inter-annual variability in weather conditions as crops are frequently exposed to different weather extremes within the same season. Therefore, agricultural research must strive to develop new crop varieties with inbuilt resilience towards variable weather conditions rather than merely tolerance to individual stresses in a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…South Asia region has been identified as one of the hot-spot regions for climate change effects; therefore, without sufficient adaptation measures, the region is likely to suffer negative impacts of the climate change 5 . During the past 2 decades, Asian tropics have experienced frequent episodes of extreme weather events including increased day/night temperatures, apart from scattered drought/heat stress periods almost every year in one or another country of South Asia 6 . Impact assessment of climate change effects on maize in South Asia showed that heat stress affected areas of South Asia will increase significantly under future climates, especially in the pre-monsoon season (spring) and in monsoon season 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…South Asia region has been identified as one of the hot-spot regions for climate change effects; therefore, without sufficient adaptation measures, the region is likely to suffer negative impacts of the climate change 5 . During the past 2 decades, Asian tropics have experienced frequent episodes of extreme weather events including increased day/night temperatures, apart from scattered drought/heat stress periods almost every year in one or another country of South Asia 6 . Impact assessment of climate change effects on maize in South Asia showed that heat stress affected areas of South Asia will increase significantly under future climates, especially in the pre-monsoon season (spring) and in monsoon season 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The temperatures above 40 °C during the reproductive stage can cause irreversible physiological damage and severely affect grain yield 8 , 9 . In view of recent climate change patterns in the lowland tropics, heat stress alone and in combination with drought, has emerged as one of the major production constraints for maize in several maize-dependent countries 6 , 10 . Lobell and Burke 11 showed that an increase of 2 °C temperature would result in a greater yield penalty in maize crop than a 20% decrease in precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…In central India, sowing of maize crops between the 7th and 14th of July could reduce the impact of temperature on maize grain and biomass yield. The new maize germplasm is targeted for stress-prone environmental conditions (11).…”
Section: Effect Of Temperature On Growth and Yield Parameters Of Maizementioning
confidence: 99%
“…The optimization of the planting window (changing planting dates, selection of cultivars) for utilizing solar radiation is an eco-friendly and low-cost adaption strategy (9,10). Similarly, stressresilient new germplasm of maize is discovered to achieve yield potential with a reduction in the risk concerning climate change (11). This review presents the latest systematic data published between 2000-2022 based on planting dates and climate change strategies for maize.…”
Section: Introductionmentioning
confidence: 99%
“…Maize, a widely adopted crop under a range of climatic conditions, is often planted on salt-affected fields, as many farmlands are salinized ( Zaidi et al, 2020 ; Prasanna et al, 2021 ). Analyzing the salt tolerance mechanism in maize by studying the diverse maize germplasm and understanding the genetic architecture of salinity tolerance can guide breeding programs aimed at developing salt-tolerant maize varieties ( Luo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%